Alice in Wonderland versus "Alice in Wonderland": Praktik Apropriasi Dalam Teks (Komik) Poskolonial - Anggoro, Albertus Rusputranto Ponco (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
Children's novel Alice's Adventures in Wonderland by Lewis Carrol (fisrt published in 1865 in England) is one of the literary works of the 19th century which still popular as tales children. A myth that, once created the film version (1903), better known by the title of Alice in Wonderland represents the spirit of colonialism and imperialism. Alice's Adventures in Wonderland represent peoples of Europe who sailed the seas, explore alien worlds without a map that led to the occupation; Alice is a nation of "civilized" that comes in foreign lands., whisch they consider to disorder and "uncivilized", for make it civilized. Emerging resistance-cultural rsistance by the colonized, among which are appropriatied of colonial texts. They do imitation (mimicry) to mock (mockery). In the perspective of postcolonial resistance-resistance was studied and identified to understand the impacts of colonialism that still exists today. Comic / manga works Katherin alice in Wonderland is practice of appropriation : comics / manga that made a lot of time post-colonial after political decolonization in Indonesia.Keywords :Â colonialism,imperialism,orientalism,postcolonial,abrogation,appropriation,mimicry,mockery,comics,manga